Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1089/hum.2010.008
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Directed Recombinant Adeno-Associated Viral Gene Delivery Rescues a Lethal Mouse Model of Methylmalonic Acidemia and Provides Long-Term Phenotypic Correction

Abstract: Methylmalonic acidemia is a severe metabolic disorder caused by a deficiency of the ubiquitously expressed mitochondrial enzyme, methylmalonyl-CoA mutase (MUT). Liver transplantation has been used to treat a small number of patients with variable success, and whether liver-directed gene therapy might be employed in such a pleiotropic metabolic disorder is uncertain. In this study, we examined the therapeutic effects of hepatocytedirected delivery of the Mut gene to mice with a severe form of methylmalonic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 38 publications
4
53
0
Order By: Relevance
“…Together, these findings suggest that cell and/or mitochondrial autonomous effects, rather than elevations in methylmalonic acid per se, are responsible for the hepatic mitochondrial changes and the GFR decrease associated with proximal tubular mitochondrial dysfunction. This challenges previous theories about methylmalonate as a toxic agent (21,22) and further supports observations from gene therapy studies showing that the long-term correction of Mut −/− mice is mediated by a small number of stably transduced cells (13,23). The concept that a kidney with normal Mut activity may be protected from MMA nephrotoxicity is reinforced by a recent study that proposed providing renal allografts as a form of "cellular" therapy for MMA, despite the implicit knowledge that the allograft will be exposed to very high metabolite concentrations in the recipient patient (24).…”
Section: Discussionsupporting
confidence: 73%
“…Together, these findings suggest that cell and/or mitochondrial autonomous effects, rather than elevations in methylmalonic acid per se, are responsible for the hepatic mitochondrial changes and the GFR decrease associated with proximal tubular mitochondrial dysfunction. This challenges previous theories about methylmalonate as a toxic agent (21,22) and further supports observations from gene therapy studies showing that the long-term correction of Mut −/− mice is mediated by a small number of stably transduced cells (13,23). The concept that a kidney with normal Mut activity may be protected from MMA nephrotoxicity is reinforced by a recent study that proposed providing renal allografts as a form of "cellular" therapy for MMA, despite the implicit knowledge that the allograft will be exposed to very high metabolite concentrations in the recipient patient (24).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, the activity is proved to be slightly less than CMV and EF1α, but far greater than other hepatocyte-specific promoters such as apoE and CYP2E1 promoters. The TBG promoter has been increasingly and successfully applied in correction of genetic diseases such as mucopolysaccharidosis, muscular dystrophy and methylmalonic acidaemia (Carrillo-Carrasco et al 2010;Bish et al 2011;Cotugno et al 2011) and demonstrated to be efficient in treating FH in this study.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to the AAV-treated cohorts, a control group of untreated Mut +/-mice (n = 51) was followed in parallel for 18 to 25 months, with only 3 mice developing HCC (<10%) (Figure 1B and transgenes were highly effective at rescuing the neonatal lethal phenotype displayed by mice with MMA (25)(26)(27)(28). In the present studies, these large cohorts of treated and control mice were followed for 22 months to monitor the efficacy of neonatal AAV gene therapy and survey for long-term complications.…”
Section: Introductionmentioning
confidence: 99%